Rethinking multicultural education for the next generation : the new empathy and social justice - Dolby, Nadine (New York : Routledge, 2012)
Rethinking Multicultural Education for the Next Generation builds on the legacy of social justice multicultural education, while recognizing the considerable challenges of reaching todays college students. By drawing on breakthrough research in two fields neuroscience and animal studies Nadine Dolby argues that empathy is an underlying element of all living beings. Dolby shows how this commonality can provide a scaffolding for building an exciting new approach to developing multicultural and global consciousness, one that has the potential to transform how our students see and relate to the world around them. This book features classroom vignettes and reflections, discussion of research with pre-service teachers on the concept of empathy, and pedagogical suggestions for fostering the new empathy in students. Incorporating discussions of animal emotions, sustainability, and our responsibilities to all living creatures and the planet, Dolby challenges multicultural educators to rethink both curriculum and pedagogy and to begin new and bolder conversations about how empathy for humans, animals, and the planet must be part of a new approach to teaching.
Includes bibliographical references and index.
Keywords: Multicultural education; Social justice -- Study and teaching